Planarization engineering of benzodithiophene-based nanogrids for enhanced carrier mobility and emission performance - Lei Yang; Jun Yang; Shi-rui Chen; Wen-bin Xie; Cong Sun; Wang-yang Wu; Xin-zhe Peng; Manas Ranjan Dash; Xue-qin Ran; Mohamad Akbar Ali; Ling-hai Xie (Chemical Engineering Journal, 2026)

Apoptotic vesicle-hybridized nanosponges enable dual-phase immunomodulation for targeted periodontitis therapy - Xiao-Ru Xu; Xin-Yan Luo; Lu-Fan Yang; Fei-Ran Wang; Jia-Wei Lu; Bai-Ting Luan; Yuan Yuan; Zi-Qi Zhang; Jin-Yu Liu; Yuan-Yuan Li; Yi-Han Liu; Yu Fu; et al. (Chemical Engineering Journal, 2026)

Climate value of energy storage for floating photovoltaic across China’s decarbonizing power grids - Ran Hao; Xin Sun; Yuchen Zhao; Chengchao Huang; Lili Yang; Weiqiao Wang; Junyu Sun; Li Fei; Lihao Zhao (ENGINEERING Environment, 2026)

Crystalline covalent organic frameworks (COFs) for synergistic NO2 physisorption and chemisorption - Huimin Chen; Xin Li; Lihong Ran; Chenguang Li; Dabin Liu; Binbin Wang (Journal of Environmental Chemical Engineering, 2026)

Elucidating the thermal degradation of fish oil and algal oil: A comparative study on the evolution of flavor profiles and lipid oxidative pathways - Shuang Cui; Ran Xin; Bo Wang; Tingting Zhang; Xuhui Huang; Lei Qin (Food Research International, 2026)

Sulfate as a regulator of Bacteroides thetaiotaomicron glutamate decarboxylase: Elucidating the bipartite binding and regulation mechanism - Shujun Liu; Yulu Wang; Boting Wen; Ran Ran; Haiyan Yu; Abeer Mohamed; Xue Han; Zhen Li; Fengjiao Xin (Food Chemistry, 2026)

RETRACTED: Metastable conformational regulation in heat-induced gluten aggregation: multiscale experiments and molecular dynamics reveal distinct roles of HMW-GS at the Glu-B1 locus - Bo Wang; Ping-ping Zhang; Rong-ran Zhang; Tian Lv; Yue Zhang; Pei Wang; Qin Zhou; Dong Jiang; Xin-long Dai; Hao Jiang; Tao Yang (Food Hydrocolloids, 2026)

Steering active hydrogen in PtCu single atom alloy nanowires for efficient nitrate reduction to ammonia - Weimian Zhang; Binwen Zeng; Haoliang Huang; Fan Dang; Xin Liu; Jing Sun; Wei Liao; Mengxiang Han; Chao Song; Run Ran; Kaiyang Xu; Fei Lin; et al. (Chemical Engineering Journal, 2026)

The role of transcription factor MdGeBP3 in Modulating cold stress tolerance and anthocyanin biosynthesis in apple - Ming-Kun Wang; Ran-Xin Liu; Cong-Yu Xu; Yue-Ning Wang; Xiao-Han Qin; Shan-Shan Li; Ying-Xue Lv; Du Liu; Jie Lu; Xiao-Fei Wang (Journal of Plant Physiology, 2026)

Top-down vitrimerization of commercial polymer materials: A practical pathway toward sustainability - Xiaming Feng; Shenghua Yang; Wenkang Zhou; Hongyu Yuan; Jiaxin Ran; Hongyu Yang; Cheng Yan; Xin Wang (Chemical Engineering Journal, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Omics-assisted genetic dissection and coordinated improvement of apple flesh color, flavor, and fruit size - Nan Wang; Wenjun Liu; Xuelian Han; Zhiqiang Li; Xin Jing; Zongying Zhang; Hongcheng Fang; Shuhui Zhang; Haifeng Xu; Qi Zou; Lei Yu; Tongyao Xu; et al. (Molecular Plant, 2026)

Association study on the regulation of muscle development-related genes, proteins, and metabolites in different tissues by gastrointestinal flora during various developmental stages of Liaoning cashmere goats - Yinggang Sun; Xingtang Dou; Qingyu Yuan; Ran Duan; Qiying Zhan; Taiyu Hui; Yanjun Qiao; Jiaqi Li; Wangshu Li; Yunlong Guo; Dakun Lyu; Jiaqi Ge; et al. (Food Chemistry, 2026)

Retraction notice to “Metastable conformational regulation in heat-induced gluten aggregation: multiscale experiments and molecular dynamics reveal distinct roles of HMW-GS at the Glu-B1 locus” [Food Hydrocolloids 179 (2026) 112791] - Bo Wang; Ping-ping Zhang; Rong-ran Zhang; Tian Lv; Yue Zhang; Pei Wang; Qin Zhou; Dong Jiang; Xin-long Dai; Hao Jiang; Tao Yang (Food Hydrocolloids, 2026)

TRIF signaling is essential for the activation of dendritic cells during porcine rotavirus infection - Yu Sun; Tianming Niu; Ran Zhang; Danni Li; Mingyang Cheng; Chenxi Jiang; Yiran Shao; Hongyuan Wang; Ziqun Guo; Wentao Yang; Xin Cao; Chunfeng Wang; et al. (Veterinary Microbiology, 2026)

Study on temperature evolution and associated phase behavior inside an industrial-scale large-diameter test pipeline during liquid CO₂ discharge - Xin Ouyang; Zichao Hu; Tao Wang; Qiqi Liu; Sheng Sun; Ran Sun; Shiqi Ge; Zhenyi Liu (Process Safety and Environmental Protection, 2026)

Peak greening at moderate shrinking intensity across Chinese counties - Ran Chen; Wenxiao Jia; Kai Wang; Xinyuan Zhang; Jiaxuan Xin; Wenjian Li; Zhijun Zhang; Junling He (Journal of Environmental Management, 2026)

Algal community composition drives lake greenhouse gas emissions via dissolved organic matter transformation and microbial processing - Weiqiao Wang; Xin Sun; Ran Hao; Fei Li (Journal of Environmental Management, 2026)

Waste-to-waste synergistic regenerative combustion of ultra-low concentration methane and coal gangue in fluidization: Multi-parameter coupling effects - Ziwei Hu; Qingxiang Wang; Ran Xu; Xin Xu; Ding Wang; Xiao Yang; Yaojie Tu (Environmental Research, 2026)

Ion-specific multiscale regulation of gelatinization and retrogradation in normal and waxy wheat starches: Cooperative roles of valence, hydration, and molecular chain architecture - Tian Lv; Xin-rong Lv; Shu-ning Yuan; Yu Hu; Rong-ran Zhang; Yue Zhang; Chuan Zhong; Pei Wang; Qin Zhou; Dong Jiang; Hao Jiang; Tao Yang (Food Hydrocolloids, 2026)

Single-cell sequencing reveals metabolic reprogramming and immune regulation underlie the maintenance of teleost granulomas - Zheng-Yang Zhou; Zheng-Ran Jian; Jin-Lai Gu; Xin-Yuan Jiang; Jie He; Yuan-Chang Gao; Sheng Lian; Shang-Jie Bai; Chen-Wang Lu; Lin-Feng Kuang; Ming-Zhu Liu; Peng-Fei Li; et al. (Fish & Shellfish Immunology, 2026)

Effects of ultrasound and pullulanase dual modification on the structure and physicochemical properties of cassava starch and its films - Wen-Jie Ren; Qin Yang; Xin-Ran Wang; Han-Qing Chen (Food Chemistry, 2026)

Near-surface ground ice map of the Northern Hemisphere - Bingquan Wang; Youhua Ran; Xin Li; Jan Hjort; Olli Karjalainen; Qingbai Wu; Yu Sheng; Huijun Jin; Defu Zou; Lin Zhao; Rui Ma; Ziyong Sun; et al. (Science Bulletin, 2026)

Integrated metabolomic and transcriptomic analyses unravel the function of quercetin in enhancing grape resistance to anthracnose - Meng-Fei Li; Ming-Yi Wang; Fu-Lai Han; Zhe Zhang; Ya-Lin Liu; Meng-Ran Li; Yu-Fei Li; Jie Yang; Xin Liu; Guang-Chao Liu (Postharvest Biology and Technology, 2026)

Porous MXene nanoplatform with ultrahigh drug loading for synergistic photothermal/photodynamic therapy and drug resistance reversal in osteosarcoma - Zhen Song; Ran-Ran Zhang; Zi-Chao Yan; Jie Wang; Youchang Liu; Chang-Qing Jiang; Meng Qiu; Bing-Xin Zheng; Bin Yue (Chemical Engineering Journal, 2026)

Overexpression of PtrPYL11 enhance drought tolerance in Populus: evidence from genome-wide identification and comparative transcriptome profiling - Shuang-Lian Deng; Shu-Ying Wei; Rui-Quan Wang; Yuan Zhang; Hao Li; Xing-Yu Liu; Xin-Ran Yu; Guan-Ru Ren; Ting Wang; Fang He (Plant Cell Reports, 2026)

Targeting ACSL4: A potential strategy to alleviate deoxynivalenol-mediated intestinal ferroptosis, oxidative stress, and immunosuppression in Channa argus - Yi-Ran Zhao; Tong-Hao Wang; Ze-Xin Zhao; Xiao-Tian Niu; Hong-Ming Lv; Yan-Bing Li; Yang Cao; Mu-Yang Li (Aquaculture, 2026)

Emergence of a novel porcine reproductive and respiratory syndrome virus strain inducing biphasic temperature fluctuations in Tianjin, northern China - Jia Wang; Yi-Han Lu; Bo-Han; Hai-Tao Yang; Xin-lei Li; Wen Sun; Shi-Qin Zhang; Zhuo-Ran Miao; Xue-Jiao Cheng; Chun-Xue You; Ying-Feng Sun (Research in Veterinary Science, 2026)

Winter CO2 temporal variations in a northern temperate bay: role of biological processes - Hanyang Wang; Hao Qiao; Ming Xin; Faisal Hamzah; Mingrui Li; Yunxiao Li; Qinsheng Wei; Xiangbin Ran; Liang Xue (Marine Environmental Research, 2026)

MdHMGB15 enhances zinc tolerance by activating multiple metal homeostasis genes in apple - Ran-Xin Liu; Ming-kun Wang; Yue-Ning Wang; Xiao-Han Qin; Ying-Xue Lv; Shan-Shan Li; Du Liu; Cong-Yu Xu; Xiao-Fei Wang (Journal of Hazardous Materials, 2026)

Uncovering pH-driven metastable transitions and thermal aggregation of HMW-GSs via all-atom molecular dynamics simulations - Tao Yang; Rong-ran Zhang; Xin-rong Lv; Tian Lv; Bo Wang; Yue Zhang; Pei Wang; Qin Zhou; Dong Jiang; Zhe Liu; Hao Jiang (Food Hydrocolloids, 2026)

Deciphering the regulatory role of the pfs gene on biofilm formation in Lactobacillus plantarum R: Insights from transcriptome and metabolome - Xin Fan; Bo Li; Xinao Xu; Binbin Long; Zhiwen Jia; Ran Wang; Junjun Gao; Yang Chen; Mingye Peng; Mengzhou Zhou (Bioresource Technology, 2026)

Unveiling the molecular mechanisms of dihydromyricetin regulating the biosynthesis of three key secondary metabolites in Monascus purpureus HBSD08 through integrated transcriptomic and metabolomic analyses - Ran Fang; Yingying Wang; Jie Qiao; Di Wu; Qianyu Gao; Chunzheng Han; Penghui Sun; Wanting Wang; Xin Zeng; Bingyue Xin; Biao Zhang; Deyin Zhao; et al. (Food Bioscience, 2026)

Advanced functionalization strategies of chitin and chitosan toward sustainable nanocomposites - Shuang-Lin Zou; Xin-Ran Liu; Jia-Hui Zhang; Ying-Chun Xu; Qiang Wang; Ling-Ping Xiao; Run-Cang Sun (Carbohydrate Polymers, 2026)

Tree of life and conservation of gymnosperms in China - Chang-Wang Ma; Dan Xie; Hong Du; Kai-Yuan Huang; Yuan-Yuan Feng; Zhou-Rui Wei; Xin-Quan Liu; Cheng-Ru Li; Jing-Jing Sun; Xiao-Xin Wei; Zhi-Heng Wang; Wei-Hua Xu; et al. (Science China Life Sciences, 2026)

Rhein Prevents APAP-induced drug-induced Liver Injury by Upregulating Nrf2 and Inhibiting APAP-activating Enzymes - Mingda Liu; Jin Dai; Liangding Dou; Zifeng Deng; Junxian Liu; Xin Hou; Jinwen Zhang; YongChao Huang; Zhi Huang; Dai Wang; Dongbei Guo; Ran An; et al. (Cell Biochemistry and Biophysics, 2026)

Bacterial, viral and environmental interactions shape antibiotic resistance genes in China's anaerobic-anoxic-oxic wastewater treatment systems - Qian Liu; Jie Chen; Ran Xu; Cong Huang; Nanqi Ren; Shuhong Gao; Wei Li; Xiaodong Xin; Sihao Lv; Siqi Yang; Weiwei Ben; Ai-Jie Wang (Water Research, 2026)

Bio-based anhydride crosslinked furan-derived vitrimeric epoxy networks with intrinsic flame retardancy, self-healing capacity and recyclability - Tian-Mo Yang; Hao-Xin Niu; Wen-Jie Zheng; Hao-Ran Jiang; Yuan Hu; Xin Wang (Journal of Cleaner Production, 2026)

Contribution of lakes to global greenhouse gas emissions: Mechanisms, quantification and mitigation strategies - Weiqiao Wang; Xin Sun; Xue Zhu; Ran Hao; Fei Li (Journal of Environmental Management, 2026)

Close-packed metal organic frameworks enabled high-energy solid-state lithium metal batteries - Yining Zhang; Hongsheng Shi; Yuyao Zhang; Xin Chen; Shuanghong Wang; Jinjiang Liang; Qiong Yuan; Tianyi Gao; Ran Wei; Haochen Zhang; Tao Li; Tianquan Lin; et al. (Chemical Engineering Journal, 2026)

DLP 3D printing of high-performance thermosetting polymers with photothermal dual-curing resin containing reversible covalent bonds - Lingyu Zhao; Pengyi Wang; Xiaojuan Zhao; Xin Yang; Ying Zhang; Bing Cheng; Wei Huang; Ran Yu (Chemical Engineering Journal, 2026)

Nicotinamide delays browning in fresh-cut apples through reducing Chlorogenic acid and inhibiting PPO activity - Chen Wang; Lu-Ping Dai; Xin-Ran Bai; Song Zhang; Pei-Qiang Dai; Bao-Long Zhao; Feng-Yun Zhao; Da-Gang Hu (Food Chemistry, 2025)

Machine learning-assisted identification of core flavor compounds and prediction of core microorganisms in fermentation grains and pit mud during the fermentation process of strong-flavor Baijiu - Jiang Xie; Jiaxin Hong; Chunsheng Zhang; Xin Yuan; Zhigang Zhao; Dongrui Zhao; Shimin Wang; Baoguo Sun; Ran Ao; Jinyuan Sun; Yuling Sun; Mingquan Huang; et al. (Food Chemistry, 2025)

Ultra-tough and autonomous self-healing polyurethane based on dynamic pyrrolidine-urea bonds and their coordination complex - Lingyu Zhao; Pengyi Wang; Pingxia Zhang; Xiaojuan Zhao; Xin Yang; Ying Zhang; Bing Cheng; Wei Huang; Ran Yu (Chemical Engineering Journal, 2025)

In-situ formation of green rust during Fe(II) coagulation: Dual reductive and adsorptive pathways for dyeing wastewater treatment - Xian Zhao; Jia-Yi Wang; Yu-Qian Wang; Chen-Hao Cui; Xin Yan; Wei Dai; An-Ran Zhang; Zhen-Ying Zhang; Ding-Ding Tang; Yan Zhou; Qiong Qin; Ji-Wei Pang; et al. (Water Research, 2025)

A copper-based single-atom material effectively controls plant diseases with nearly zero soil residue and low phytotoxicity - Rui Huang; Yong Yan; Yafei Jiang; Chunyan Gu; Zhentao Ma; Lifang Xue; Yao Ma; Xingen Lin; Juan Zhang; Ran Shi; Yiwen Wang; Linjing Liu; et al. (Science Bulletin, 2025)

Rapid cultivation regulation of Methyl tert-butyl ether degradation consortium: Effects of supplemental carbon source and mechanism - Wenhao Guo; Sunyin Wang; Jun Gu; Zixi Ming; Wei Wang; Xin Song; Yawei Qian; Manjun Zhan; Ran Yu (Journal of Environmental Chemical Engineering, 2025)

A ratiometric fluorescent probe for sensitive detection of benzoyl peroxide and hypochlorite in food - Shun-Qiang Cui; Xin-Yi Liang; Zhi-Qiang Cai; Hou-Qun Yuan; Qiu-Yu Zhang; Yi-Fan Xia; A.K.I.M.A.N.A. Sandra; Ling-Yi Guo; Ran Wang; Shi-Yu Zhao; Yan-Xia Li; Guang-Ming Bao (Food Chemistry, 2025)

Multifunctional bending sensor based on PLA hierarchical porosity: smart wearable device with wide range response, self-powered capability and biodegradable - Jun Hou; Danqing Zhang; Qi Ran; Geran Yin; Manlin Wang; Wenhao Yang; Hua Wang; Yi Xiong; Xin Liu; Heng Pan; Liangjun Xia; Weilin Xu (Chemical Engineering Journal, 2025)

CCP domain containing protein from complement factor H of Paralichthys olivaceus has potential effects against Edwardsiella piscicida infection - Xuan-yue Wang; Yu-ting Du; Xin-yi Jiang; Zhuo-ran Ma; Chao-ran Zhang; Xue-peng Li; Zeng-zhi Yuan; Mo-fei Li (Aquaculture, 2025)

Effect of H2 content on the evolution process of CH4/H2 explosion pressure and flame structure - Shanshan Liu; Dongxu Huang; Yong Pan; Yingquan Qi; Lingxiu Yan; Zhenhua Wang; Xin Zhang; Ran Ye; Juncheng Jiang (Process Safety and Environmental Protection, 2025)

Unsteady hydrodynamic performance of a submarine with a new kind of pump-jet propulsor - Yun Ding; Xin-ran Li; Wen-Quan Wang; Guanzhe Cui; Tao Guo; Yan Yan (Ocean Engineering, 2025)

A two-level turbulent density-based topology optimization method: A low-resistance U-bend channel flow - Yan Tian; Ran Gao; Yi Wang; Angui Li; Xin Dong; Tong Li; Shengrui Yu (Building and Environment, 2025)

Asymmetric C2-functionalization of indoles via visible-light-promoted three-component reaction - Han-Peng Pan; Xiao-Ying Hu; Jun-Hui Luo; Zhao-Jie Fu; Xin-Yi Yao; Meng-Yan Ran; Fang-Xin Wang; Xiang-Zhi Zhang (Molecular Diversity, 2025)

Data-driven differentiable model for dynamic prediction and control in wastewater treatment - Yun-Peng Song; Wen-Zhe Wang; Yu-Qi Wang; Wan-Xin Yin; Jia-Ji Chen; Hao-Ran Xu; Hao-Yi Cheng; Fang Ma; Han-Tao Wang; Ai-Jie Wang; Hong-Cheng Wang (Water Research, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Independent and joint effects of volatile organic compounds on pulmonary function in U.S. adults from NHANES: the mediating role of platelet-to-lymphocyte ratio - Yan-Fei Wei; Hao-Wen Chen; Kuan Liu; Shi-Ao Wang; Wei-Dong Fan; Zhan-Hui Shao; Bi-Fei Cao; Yong-Qi Liang; Zheng-Yun Xu; Kai-Yue Liao; Zi-Xuan Zhao; Lu-Rong Yang; et al. (Environmental Pollution, 2025)

A green-solvent processed multifunctional bamboo composite with high strength, robust fire retardancy, and dimensional stability - Xiangyu Ren; Huijun Zhang; Weibing Xue; Tongda Liu; Rong Liu; Xin Ran; Ping Wang; Wei Gao; Yanmei Li; Guanben Du; Long Yang (Chemical Engineering Journal, 2025)

Exploring the impact of cuproptosis-related genes on immune infiltration in rheumatoid arthritis - Fang Xu; Xin-ran Hu; Yuan Wang; Xi-fan Mei (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

The application of marine bioactive composite materials in environmental remediation - Yanan Huang; Hao Li; Ronglian Xing; Xiaorui Chen; Yuxin Sun; Meichen Tian; Ran Zhang; Xin Wang; Xinxin Wang; Rui Li; Lihong Chen; Hongxia Zhang; et al. (Desalination, 2025)

How the dispersion and coalescence behaviors of CO2 bubbles affecting carbonation reaction in bubble column reactor: experimental and numerical simulation study - Lin Chen; Jintao Ma; Cheng Chen; Xin Wang; Yonghong Qin; Enze Li; Yanxia Guo; Ran Peng; Zihe Pan (Chemical Engineering Journal, 2025)

A genomic variation map provides insights into potato evolution and key agronomic traits - Qun Lian; Yingying Zhang; Jinzhe Zhang; Zhen Peng; Weilun Wang; Miru Du; Hongbo Li; Xinyan Zhang; Lin Cheng; Ran Du; Zijian Zhou; Zhenqiang Yang; et al. (Molecular Plant, 2025)

Corrigendum to “Molecular characterization of condensates altered by thermochemical sulfate reduction and evaporative fractionation using high-resolution mass spectrometry” [Fuel 381 (2025) 133732] - Dongyong Wang; Jianfa Chen; Meijun Li; Jianxun Wu; Quan Shi; Wenqiang Wang; Shuofan Li; Zichao Ran; Zi’ao Geng; Xin Wang; Huiqiang Qin; Xianli Zou; et al. (Fuel, 2025)

Parkinson's Disease and the Microbiota-Gut-Brain Axis: Metabolites, Mechanisms, and Innovative Therapeutic Strategies Targeting the Gut Microbiota - Zhao Ran; Ben-Rong Mu; Dong-Mei Wang; Xin-Huang; Quan-Hong Ma; Mei-Hong Lu (Molecular Neurobiology, 2025)

The Arabidopsis heterotrimeric G protein α subunit binds to and inhibits the inward rectifying potassium channel KAT1 - Jiang-Fan Guo; Hui Zhou; Zhuo-Ran Hu; Ya-Lan Yang; Wen-Bin Wang; Yan-Ru Zhang; Xue Li; Nuerkaimaier Mulati; Ying-Xin Li; Lu Wu; Yu Long; Jun-Min He (Plant Science, 2025)

Molecular characterization of condensates altered by thermochemical sulfate reduction and evaporative fractionation using high-resolution mass spectrometry - Dongyong Wang; Jianfa Chen; Meijun Li; Jianxun Wu; Quan Shi; Wenqiang Wang; Shuofan Li; Zichao Ran; Zi’ao Geng; Xin Wang; Huiqiang Qin; Xianli Zou; et al. (Fuel, 2025)

Enhanced catalytic decomposition of methyl formate to carbon monoxide and methanol using palladium/activated carbon catalyst: Mechanistic insights and catalyst design considerations - Wei Shen; Xin Zhang; Yuanyuan Huang; Liyuan Xu; Ran Wang; Wenxing Yang; Pengbin Pan; Yuan-Gen Yao (Fuel, 2025)

Anaerobic co-digestion of winery wastewater with sewage sludge for methane production: Complementary feedstocks and potential direct interspecies electron transfer - Zhixuan Ma; Lifang Yu; Ze Wang; Xin Tian; Lanxiang Zheng; Ran Liu (Fuel, 2025)

Effects of decapitation on yield-related traits of total node number per plant in soybean - Ran Fang; Yichun Wu; Xin Huang; Zhihong Hou; Jialin Zhang; Lingshuang Wang; Yanan Wang; Yaru Li; Liyu Chen; Hui Yang; Lin Yue; Haiping Du; et al. (Field Crops Research, 2025)

Topology optimization of bend for reducing the local resistance in a piping and duct system - Yan Tian; Ran Gao; Ruoyin Jing; Yi Wang; Angui Li; Xin Dong; Xinpeng Hao; Zheng Ji (Building and Environment, 2025)

RGS22 maintains the physiological function of ependymal cells to prevent hydrocephalus - Xue Pang; Lin Gu; Qiu-Ying Han; Jia-Qing Xing; Ming Zhao; Shao-Yi Huang; Jun-Xi Yi; Jie Pan; Hao Hong; Wen Xue; Xue-Qing Zhou; Zhi-Hui Su; et al. (Science China Life Sciences, 2025)

Sleep deprivation stimulates adaptive thermogenesis by activating AMPK pathway in mice - Tian-Shu Zheng; Xin-Ran Gao; Rui-Ping Xu; Yi-Fei Zhao; Zhi-Teng Yang; De-Hua Wang (Journal of Comparative Physiology B, 2025)

Key process of ethanol hydrogen donor promoting the conversion of organic matter in sludge to bio-oil - Quxiu Dai; Linglong Zeng; Qihong Cen; Wang Du; Ping Ning; Kai Li; Zhiying Guo; Ran Ao; Longgui Xie; Nanqi Ren; Liping Ma; Jie Yang; et al. (Water Research, 2025)

Evaluation of the nutritional quality of yeast protein in comparison to animal and plant proteins using growing rats and INFOGEST model - Xin Cao; Hongjuan Liu; Miao Yang; Kanmin Mao; Xinzheng Wang; Ziyu Chen; Mingqi Ran; Liping Hao (Food Chemistry, 2025)

Synergistic structural engineering and electronic modulation enhance upconversion emission and charge separation in LiYF4: Yb3+, Tm3+@LiYF4:Nd3+@LixTi1-xO2 core-shell nanostructure for efficient near-infrared photocatalysis - Yuxiang Xin; Jianru Wang; Ran Jia; Chaochao Dun; Zhuolei Zhang (Chemical Engineering Journal, 2025)

A stab-/solvent-resistant HAG/silicone armor for durably stretchable electroluminescent device - Jun-Yue Li; Xin-Kai Qian; Qi-Ye Wang; Hong-Chao Sun; Xiu-Juan Li; Zhen-Yu Zhang; Chao-Ran Huang; Rui Guo; Fei Xiu; Ju-Qing Liu (Chemical Engineering Journal, 2025)

Multiphysics simulation and optimization of the in-situ beneficiation process of ilmenite minerals from lunar regolith - Peng Zhang; Xin Liu; Guanghui Liu; Wei Dai; Hanzhe Yang; Haibo Zheng; Zhi Wang; Ran Niu; Yifan Bai; Yang Zhang; Chengbao Liu; Ge Yang; et al. (Science China Earth Sciences, 2025)

Yunchengibacter salinarum gen. nov., sp. nov., a novel bacterium of the family Kordiimonadaceae isolated from sediment in Yuncheng salt lake - Hao-Ran Guo; Fan Wang; Hui-Ying Yu; Chuan-Xu Wang; Zhuo Wang; Bao-Zhu Fang; Xin Li; Wen-Jun Li (Antonie van Leeuwenhoek, 2025)

Biodegradation of imidacloprid and diuron by Simplicillium sp. QHSH-33 - Ke Xu; Xin-Ran Ke; Wan-Ting Zhang; Xin-Yuan Wu; Zhi-Jun Song; Mei-Juan Jiao; Xiao-Juan Gao; Li Zhou; Hong-Yan Ji; Fang Wang; Xiu-Li Wu (Pesticide Biochemistry and Physiology, 2024)

Optimizing LaNiO3 catalysts with urea-assisted sol-gel synthesis for dry reforming of methane - Huayu Qiu; Kang Hui Lim; Zhiliang Ou; Claudia Li; Yuan Wang; Lei Tang; Xin Huang; Jingyu Ran; Sibudjing Kawi (Journal of Environmental Chemical Engineering, 2024)

CRISPR/Cas13a-mediated visual detection: A rapid and robust method for early detection of Nosema bombycis in silkworms - Yi-Xiang Wu; Samreen Sadiq; Xin-Hao Jiao; Xue-Min Zhou; Lu-Lai Wang; Xin-Ran Xie; Iltaf Khan; Ping Wu (Insect Biochemistry and Molecular Biology, 2024)

Cost-Effective multifunctional bilayer structural hydrogel evaporator for stable solar desalination and wastewater treatment - Xin-Yu Zhou; Shu-Chao Song; Wen-Xiu Wang; Hui-Ran Jin; Shan Yun; Ai-Bin Huang; Jing Chen (Chemical Engineering Journal, 2024)

The role of Nocardia seriolae-induced autophagy in the development of chronic inflammation in the liver and the formation of granulomas in largemouth bass (Micropterus salmoides) - Shang-Jie Bai; Zheng-Ran Jian; Sheng-Yu He; Lin-Feng Kuang; Zheng-Yang Zhou; Chen-Wang Lu; Zhen-Dong Zhong; Jie He; Quan-Xin Xiong; Shuang-Yan Xiao; Peng-Fei Li; Ming-Zhu Liu; et al. (Aquaculture, 2024)

Investigation of the self-propulsion performance of a submarine with a pump-jet propulsor in a surface wave–current coupling environment - Yun Ding; Xin-ran Li; Yan Yan; Wen-Quan Wang (Ocean Engineering, 2024)

Half substitution of mineral N with fish protein hydrolysate enhancing microbial residue C and N storage and climate benefits under high straw residue return - Jia Lin Wang; Xin Yu Liu; Pei Kun Jiang; Qiu Ran Yu; Qiu Fang Xu (Journal of Environmental Management, 2024)

Impacts of nano- and micro-plastics exposure on zooplankton grazing, bacterial communities, and dimethylated sulfur compounds production in the microcosms - Yu Jiang; Juan Yu; Rong Chen; Su Wang; Gui-Peng Yang; Long-Fei Liu; Xin-Ran Song (Environmental Pollution, 2024)

Mitigating interfacial recombination enabling efficient semitransparent organic photovoltaics - Hailin Yu; Jiayu Wang; Yuanhao Li; Tianyu Liu; Yufei Gong; Cenqi Yan; Qichao Ran; Qun Luo; Zupan Mao; Xin Wei; Lei Meng; Changqi Ma; et al. (Chemical Engineering Journal, 2024)

Soil organic phosphorus is mainly hydrolyzed via phosphatases from ectomycorrhiza-associated bacteria rather than ectomycorrhizal fungi - Jing Yuan; Rui Yan; Xueqiong Zhang; Kai Su; Hui Liu; Xin Wei; Ran Wang; Lanlan Huang; Nianwu Tang; Shanping Wan; Wei Liu; Hans Lambers; et al. (Plant and Soil, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Characteristics of corn starch/polyvinyl alcohol composite film with improved flexibility and UV shielding ability by novel approach combining chemical cross-linking and physical blending - Hao-Nan Wei; Xin-Yue Liu; Chen-Chen Wang; Ran Feng; Bao Zhang (Food Chemistry, 2024)

Visual environment in schools and student depressive symptoms: Insights from a prospective study across multiple cities in eastern China - Xiyan Zhang; Jiawen Tang; Yan Wang; Wenyi Yang; Xin Wang; Ran Zhang; Jie Yang; Wei Lu; Fei Wang (Environmental Research, 2024)

Robust fatigue markers obtained from muscle synergy analysis - Chen Zhang; Zi-jian Zhou; Lu-yi Wang; Ling-hua Ran; Hui-min Hu; Xin Zhang; Hong-qi Xu; Ji-peng Shi (Experimental Brain Research, 2024)

Geochemistry and geochronology of the Ordovician Qianhe metabasalt in Northwest China: implications for the northern boundary of Qinling Orogenic Belt in heavily loess-covered regions - Xin Han; Xiaohan Huang; Ran Wang; Xingwei Wang; Yonghui Xin; Yue Li; Zhexuan Jiang (Geosciences Journal, 2024)

Experimental evidence that nitrogen-fixing cyanobacterium Trichodesmium spp. supplies new nitrogen source to marine phytoplankton - Shuang-Qing Li; Yan Xiao; Hai-Long Huang; Zhen Luo; Tao-Ran Sun; Hua-Yang Gao; Xin-Wei Wang; Hai-Bo Jiang (Frontiers in Marine Science, 2024)
In oligotrophic oceans, primary productivity is widely limited by nitrogen bioavailability. The broadly distributed and abundant nitrogen-fixing cyanobacterium Trichodesmium plays an important role in the oceanic nitrogen and carbon cycles by providing a “new” source of nitrogen to many non-diazotrophic microbes, thereby driving new primary production in the ocean. However, the underlying process and mechanism of nitrogen supply from Trichodesmium to other phytoplankton remain unclear. Here, our results demonstrated that the fixed nitrogen released by Trichodesmium could sustain the growth of a non-nitrogen-fixing cyanobacterium Synechococcus sp. PCC 7002, including a mutant strain (Mut- ureA ) that cannot use urea. However, the growth rate of Mut- ureA was approximately 20% lower than that of the wild strain when Trichodesmium filtrate was used for nitrogen supply. This result was consistent with the composition of the Trichodesmium exudate, in which urea comprised more than 20% of the total fixed nitrogen that was released. It is evident from the experiments that a fraction of the Trichodesmium -derived nitrogen was not available to Mut- ureA . Our results suggested that Trichodesmium produces dissolved organic nitrogen, especially a certain amount of urea as a “new” nitrogen source, benefiting in particular populations of surrounding phytoplankton species.

Mitochondrial damage and activation of NLRP3 induced by Yersinia ruckeri infection play an important role in the occurrence of diffuse acute inflammation of channel catfish (Ictalurus punctatus) - Chen-Wang Lu; Jie He; Quan-Xin Xiong; Zhen-Dong Zhong; Bin Yang; Sheng Lian; Meng-Meng Wang; Shang-Jie Bai; Lin-Feng Kuang; Zheng-Yang Zhou; Zheng-Ran Jian; Yuan-Chang Gao; et al. (Aquaculture, 2024)

Novel insights into dimethylsulfoniopropionate cleavage by deep subseafloor fungi - Xuan Liu; Xin-Ran Wang; Fan Zhou; Ya-Rong Xue; Xiang-Yang Yu; Chang-Hong Liu (Science of The Total Environment, 2024)

The fabrication of Mn single atoms/clusters on Al2O3 for enhanced catalytic NO oxidation - Xiao-Ke Hou; Hui-Xin Zhang; Yi-Bo Wang; Jin-Ping Zhang; Xin Gao; Lei Chen; Chao Li; Hong-Mei Jing; Chi He; Qiang Lu; Chun-Ran Chang (Fuel, 2024)

Mechanical protein polycystin-1 directly regulates osteoclastogenesis and bone resorption - Mei Huang; Jingxuan Zhou; Xiaoxiao Li; Ran Liu; Yangzi Jiang; Kaixuan Chen; Yurui Jiao; Xin Yin; Ling Liu; Yuchen Sun; Weishan Wang; Ye Xiao; et al. (Science Bulletin, 2024)

Estrogen-related receptor, a molecular target against lepidoptera pests - Guan Wang Shen; Die Liu; Hao Ran Xu; Lu Yu Hou; Jin Xin Wu; Qing You Xia; Ping Lin (Pesticide Biochemistry and Physiology, 2024)

Effects of micro- and nano-plastics on growth, antioxidant system, DMS, and DMSP production in Emiliania huxleyi - Juan Yu; Ji-Yuan Tian; Yu Jiang; Xue-Dan Wang; Xin-Ran Song; Long-Fei Liu; Gui-Peng Yang (Environmental Pollution, 2024)

Reactive oxygen species (ROS) modulate nitrogen signaling using temporal transcriptome analysis in foxtail millet - Hui-Xin Meng; Yu-Ze Wang; Xin-Li Yao; Xin-Ran Xie; Shuqi Dong; Xiangyang Yuan; Xiaorui Li; Lulu Gao; Guanghui Yang; Xiaoqian Chu; Jia-Gang Wang (Plant Molecular Biology, 2024)

Rhythmic mild photothermal therapy enhancing anti-PD-L1 response for oral squamous cell carcinoma immunotherapy - Tao Liu; Shilin Guo; Dongyao Zhang; Diya Xie; Xinyu Zhang; Lin Chen; Yanyi Wang; Huihui Zou; Linzhong Yang; Meng Zhou; Xin Tong; Jianchuan Ran; et al. (Chemical Engineering Journal, 2024)

Short-term effects of exposure to cold spells on blood pressure among adults in Nanjing, China - Tian-Lin Li; Bei-Jing Cheng; Nan Jiang; Xing-Chen Meng; Chun Wang; Yang Huang; Ke Meng; Hui Li; Xin-Yi Zhu; Ran Liu (Air Quality, Atmosphere & Health, 2024)

Spatially resolved glacial meltwater retainment in glacial lakes exerts increasing impacts in High Mountain Asia - Xin Wang; Weijie Ran; Junfeng Wei; Yongsheng Yin; Shiyin Liu; Tobias Bolch; Yong Zhang; Xijing Xue; Yongjian Ding; Qiao Liu; Yanlin Zhang; Lufang He (Journal of Hydrology, 2024)

Phthalate drives splenic inflammatory response via activating HSP60/TLR4/NLRP3 signaling axis-dependent pyroptosis - Xin-Ran Ge; Yi Zhao; Hao-Ran Ren; Fu-Wei Jiang; Shuo Liu; Ming Lou; Yi-Feng Huang; Ming-Shan Chen; Jia-Xin Wang; Jin-Long Li (Environmental Pollution, 2024)

Film-Depth-Dependent Charge Mobilities in Organic Semiconductor Films - Qingyu Wang; Peng Wei; Zongze Qin; Yixin Ran; Xin Wang; Peng Zhang; Guanghao Lu (Chemical Engineering Journal, 2024)

Increasing lateral transport of soil and carbon on the Tibetan Plateau - Yanzhang Huang; Zhongbao Xin; Guangyao Gao; Xixi Lu; Lishan Ran; Yafeng Wang; Zhiqiang Zhang (CATENA, 2024)

The spatial transcriptomic landscape of human gingiva in health and periodontitis - Zongshan Shen; Ran Zhang; Yunjia Huang; Jiayao Chen; Mengjun Yu; Chunhua Li; Yong Zhang; Lingling Chen; Xin Huang; Jichen Yang; Zhengmei Lin; Songlin Wang; et al. (Science China Life Sciences, 2024)

KDM4B down-regulation facilitated breast cancer cell stemness via PHGDH upregulation in H3K36me3-dependent manner - Xin-Yu Wang; Hong-Ming Li; Ran Xia; Xiang Li; Xing Zhang; Tong-Zhao Jin; Hong-Sheng Zhang (Molecular and Cellular Biochemistry, 2024)

Modulation of pea protein isolate nanoparticles by interaction with OSA-corn starch: Enhancing the stability of the constructed Pickering emulsions - Xin-Yue Liu; Ting-Shi He; Chen-Chen Wang; Bao-Cai Xu; Ran Feng; Bao Zhang; Han Tao (Food Chemistry, 2024)

Tea polyphenols alleviate TBBPA-induced inflammation, ferroptosis and apoptosis via TLR4/NF-κB pathway in carp gills - Ran Xu; Fu-xin Han; Hong-ru Wang; Jing-jing Wang; Zhao-long Cai; Meng-yao Guo (Fish & Shellfish Immunology, 2024)

Effects of nanoplastics exposure on ingestion, life history traits, and dimethyl sulfide production in rotifer Brachionus plicatilis - Juan Yu; Su Wang; Hao-Quan Zhang; Xin-Ran Song; Long-Fei Liu; Yu Jiang; Rong Chen; Qi Zhang; Yong-Qiao Chen; Hou-Jin Zhou; Gui-Peng Yang (Environmental Pollution, 2024)

Tumor microenvironment-activated hollow vanadium-based nanoplatform for precise therapy of lung cancer through synergistically reversing cisplatin resistance - Lang Ran; Jianmin Xiao; Weijie Zhang; Miaomiao Wang; Huan Xin; Huimin Li; Hong Hao; Maoyang Wang; Xiaofei Wang; Geng Tian; Guilong Zhang (Chemical Engineering Journal, 2024)

Defect-promoted nanoparticles−nanorod Ni−NiMoO4 heterogeneous nanostructures as efficient electrocatalysts to overall water/urea splitting in fresh/sea water - Caihong Fang; Ran Li; Xin Wang; Fei Duan; Junfeng Lin; Yunqin Hu; Zhiqing Cui (Chemical Engineering Journal, 2024)

Leucine improves dietary protein use efficiency by regulating protein synthesis by activating amino acid transporters and the mTORC1 pathways in Chinese mitten crab (Eriocheir sinensis) - Ming-Qi Song; Qiu-Ran Yu; Er-Chao Li; Ying Song; Xin-Yu Cai; Yu-Xiang Huang; Chuan-Jie Qin; Xiao-Dan Wang; Jian-Guang Qin; Li-Qiao Chen (Aquaculture, 2024)

Revisiting the physical processes controlling the tropical atmospheric circulation changes during the Mid-Piacenzian Warm Period - Ke Zhang; Yong Sun; Zhongshi Zhang; Christian Stepanek; Ran Feng; Daniel Hill; Gerrit Lohmann; Aisling Dolan; Alan Haywood; Ayako Abe-Ouchi; Bette Otto-Bliesner; Camille Contoux; et al. (Quaternary International, 2024)

Conversion mechanism for solving the end-stop problem of hydraulic power take-off system for wave energy - Dahai Zhang; Chenglong Li; Ran Bi; Xin Huang; Zhiwei Sun; Tianlong Lan; Yuankui Wang; Ting Huang; Peng Qian (Ocean Engineering, 2024)

Experimental and computational insight into the role of cobalt and phosphorus in boosting Volmer and Heyrovsky steps of Ni in alkaline hydrogen evolution reaction - Wei Xu; Xian-Qing Tang; Zhen Zhang; Yi-Ran Wang; Jian-Long Luo; Isack Bulugu; Wen-Jie Yin; Xin Tang; Yu Shen (Fuel, 2024)

Na2S-modified biochar for Hg(II) removal from wastewater: A techno-economic assessment - Wenwen Zhao; Zhongsheng Zhang; Yuan Xin; Ran Xiao; Feng Gao; Haitao Wu; Wenfeng Wang; Qiang Guan; Kangle Lu (Fuel, 2024)

Voluntary running wheel exercise induces cognitive improvement post traumatic brain injury in mouse model through redressing aberrant excitation regulated by voltage-gated sodium channels 1.1, 1.3, and 1.6 - Dan Wang; Hui-Xiang Zhang; Guo-Ji Yan; Hao-Ran Zhao; Xiao-Han Dong; Ya-Xin Tan; Shan Li; Min-Nan Lu; Rong Mei; Li-Na Liu; Xu-Yang Wang; Yan-Bin Xiyang (Experimental Brain Research, 2024)
Traumatic brain injury (TBI) leads to disturbed brain discharge rhythm, elevated excitability, anxiety-like behaviors, and decreased learning and memory capabilities. Cognitive dysfunctions severely affect the quality of life and prognosis of TBI patients, requiring effective rehabilitation treatment. Evidence indicates that moderate exercise after brain injury decreases TBI-induced cognitive decline. However, the underlying mechanism remains unelucidated. Our results demonstrate that TBI causes cognitive impairment behavior abnormalities and overexpression of Nav1.1, Nav1.3 and Nav1.6 proteins inside the hippocampus of mice models. Three weeks of voluntary running wheel (RW) exercise treatments before or/and post-injury effectively redressed the aberrant changes caused by TBI. Additionally, a 10% exercise-conditioned medium helped recover cell viability, neuronal sodium current and expressions of Nav1.1, Nav1.3 and Nav1.6 proteins across cultured neurons after injury. Therefore, the results validate the neuroprotection induced by voluntary RW exercise treatment before or/and post-TBI. The RW exercise-induced improvement in cognitive behaviors and neuronal excitability could be associated with correcting the Nav1.1, Nav1.3, and Nav1.6 expression levels. The current study proves that voluntary exercise is an effective treatment strategy against TBI. The study also highlights novel potential targets for rehabilitating TBI, including the Navs proteins.

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Polyethylene microplastics cause apoptosis via the MiR-132/CAPN axis and inflammation in carp ovarian - Meng-ran Zhu; Hong-ru Wang; Fu-xin Han; Zhao-long Cai; Jing-jing Wang; Meng-yao Guo (Aquatic Toxicology, 2023)

Preliminary assessment of carbonic acid dissociation constants: Insights from observations in China's east coastal oceans - Ping Wang; Qicheng Meng; Liang Xue; Yuhang Zhao; Hao Qiao; He Hu; Qinsheng Wei; Ming Xin; Xiangbin Ran; Chenhua Han; Feng Zhou; Chunying Liu (Marine Environmental Research, 2023)

Precise classification and regional delineation of maturity groups in soybean cultivars across China - Wenwen Song; Luping Liu; Shi Sun; Tingting Wu; Haiyan Zeng; Shiyan Tian; Bincheng Sun; Wenbin Li; Lijun Liu; Shuming Wang; Han Xing; Xin’an Zhou; et al. (European Journal of Agronomy, 2023)

Kilogram-scale synthesis of carbon dots with high-efficiency full-color solid-state fluorescence using an aggregation-induced emission strategy - Hui Ding; Ran Zhao; Zi-Hui Zhang; Jia-Jia Yang; Zheng Wang; Lu-Lan Xiao; Xue-Hua Li; Xin-Jian He; Huan-Ming Xiong (Chemical Engineering Journal, 2023)

Recent progress in γ-Fe2O3-based catalysts: An overview of the synthesis and applications in environmental remediation - Yuzhuo Zhou; Xin Yang; Chen Gong; Fei Zhu; Jian Wang; Yongfeng Qi; Kai Huang; Jiang Wu; Ran Chen; Yi Liu (Chemical Engineering Journal, 2023)

Two new constituents from the aerial parts of Salvia miltiorrhiza Bge - Fan Yang; Jia Li; Xin-Lei Du; Shi-Jun Wang; Xiang-Hao Xu; Yong-Qing Zhang; Ran Yang (Natural Product Research, 2023)

Urbanization reduces soil microbial network complexity and stability in the megacity of Shanghai - Lan Liu; Zhaochen Zhang; Xin Wang; Ran Zhang; Meng Wang; Nina Wurzburger; Junxiang Li; Jian Zhang (Science of The Total Environment, 2023)

Dissolved black carbon incorporating with ferric minerals promoted photo-Fenton-like degradation of triclosan in acidic conditions - Ziyan Zhou; Hao Wu; Boming Fu; Zhe Wang; Ran Hong; Liuqing Huang; Xinyue Gu; Cheng Gu; Xin Jin (Journal of Hazardous Materials, 2023)

Late Carboniferous bimodal volcanic rocks of the West Junggar Terrane, NW China: Implications for the postcollisional tectonic setting of the southwestern CAOB - Xi Wang; Ran Wang; Pan Qu; Sanyou Cheng; Yonghui Xin (International Geology Review, 2023)

Short-term effects of cold spells on hematocrit among adults in Nanjing, China: A distributed-lagged effect analysis - Bei-Jing Cheng; Tian-Lin Li; Hui Li; Ke Meng; Xing-Chen Meng; Jia Wang; Chun Wang; Lin-Sheng Yang; Xin-Yi Zhu; Ran Liu (Science of The Total Environment, 2023)

The effect of chlorogenic acid, a potential botanical insecticide, on gene transcription and protein expression of carboxylesterases in the armyworm (Mythimna separata) - Dong-jiang Lin; Ya-xin Zhang; Yong Fang; San-ji Gao; Ran Wang; Jin-da Wang (Pesticide Biochemistry and Physiology, 2023)

Potential effects of Ag ion on the host by changing the structure of its gut microbiota - Xin-Lei Wang; Nanyang Yu; Ying-Xue Ma; Hao-Ran Zhou; Chuan Wang; Si Wei; Ai-Jun Miao (Journal of Hazardous Materials, 2023)

Black phosphorus quantum dots induced ferroptosis in lung cell via increasing lipid peroxidation and iron accumulation - Liangding Dou; Rong Liu; Zhaojizhe Wang; Zhi Huang; Lei Wang; Mo Lin; Xin Hou; Jinwen Zhang; Tantan Cheng; Qi He; Dai Wang; Dongbei Guo; et al. (Food and Chemical Toxicology, 2023)

Intervertebral disc degeneration and inflammatory microenvironment: expression, pathology, and therapeutic strategies - Xin Chen; Zihan Wang; Rongrong Deng; Hongjie Yan; Xin Liu; Ran Kang (Inflammation Research, 2023)

The spatial coordinates projection method for generating digital geologic cross sections from the multi-source terrain and geologic data - Xingwei Wang; Ran Wang; Yonghui Xin; Haidong Zhang; Xin Han; Wanshan Lei; Gangfeng Wei (Earth Science Informatics, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Strategic tillage is a promising alternative to conventional and no-tillage: Evidence from a 12-year field trial in a double-cropped rice system - Xing Wang; Cong He; Bai-Jian Lin; Xin Zhao; Ran Zhang; Ling-Tao Zhong; Xiao-Ping Xiao; Hai-Lin Zhang (European Journal of Agronomy, 2023)

A significant loop of lake sedimentation state links catchment eco‐surroundings and lake biogenic regime shifts - Fengwei Ran; Xiaodong Nie; Shilan Wang; Tao Xiao; Changrong Yang; Yi Liu; Lingxia Wang; Yaojun Liu; Xin Chu; Zhongwu Li (Limnology and Oceanography, 2023)
As an important destination for upstream materials and element accumulation, lake sediments hold a multitude of contextual information about climatic changes and anthropogenic disturbances. However, understanding the lake sedimentation state to link catchment pressures and biogenic regime shifts remains challenging. To address this, research was conducted on the lake sedimentation state, including the dynamics, catchment drivers, effects on biogenic regimes, and responses to typical historical events using nine sediment cores from Dongting Lake, China, a typical global priority ecoregion. Three transitions of lake sedimentation state were distinguished over the century (1937, 1968, and 1993), whereby hydrologic dynamics and land‐use changes in the watershed were the direct drivers with relative contributions of 16.30% and 14.56%, respectively. Lake sedimentation state and organic matter inputs not only preceded sediment biogenic elements at the shift time but also exhibited nonlinear trigger effects on biogenic element contents ( R 2 = 0.47, p

Healthy values and de novo domestication of sand rice ( Agriophyllum squarrosum ), a comparative view against Chenopodium quinoa - Pengshan Zhao; Xiaofeng Li; Hong Sun; Xin Zhao; Xiaohua Wang; Ruilan Ran; Jiecai Zhao; Yuming Wei; Xin Liu; Guoxiong Chen (Critical Reviews in Food Science and Nutrition, 2023)

A new butenolide with antifungal activity from solid co-cultivation of Irpex lacteus and Nigrospora oryzae - Ya-Mei Wu; Xue-Qiong Yang; Jing-Xin Chen; Ting Wang; Tai-Ran Li; Fan-Rong Liao; Run-Tong Liu; Ya-Bin Yang; Zhong-Tao Ding (Natural Product Research, 2023)

Degradation and filling modification of plastic waste for improvement of the slurryability of coal-plastic-water slurry - Junjie Zhai; Renfu Xu; Qihui He; Shenglin Pan; Xin Wang; Ran Zhang; Yahui Feng; Baixing Hu (Fuel, 2023)

Three-dimensional macroporous structure and surface carbon-coating modification of stainless-steel anode boost bioelectrocatalytic performance - Cheng-Yan Liu; Hao-Yi Cheng; Si-Yuan Zhai; Ran Zeng; De-Xin Zhang; Ai-Jie Wang (Chemical Engineering Journal, 2023)

Black phosphorus quantum dots induce autophagy and apoptosis of human bronchial epithelial cells via endoplasmic reticulum stress - Lei Wang; Mo Lin; Xin Hou; Liangding Dou; Zhi Huang; Rong Liu; Jinwen Zhang; Chuchu Cai; Chen Chen; Ying Liu; Dai Wang; Dongbei Guo; et al. (Chemosphere, 2023)

Ozone micro-bubble aeration using the ceramic ultrafiltration membrane with superior oxidation performance for 2, 4-D elimination - Wei-Ran Han; Wen-Long Wang; Tie-Jun Qiao; Wei Wang; Hang Su; Chen-Xin Xu; Qian-Yuan Wu (Water Research, 2023)

Chloroacetonitrile exposure induces endoplasmic reticulum stress and affects spindle assembly in mouse oocytes - Feng-Xin Qiao; Ming-Xin Sun; Zhi-Ran Xu; Yue-Cen Liu; Yan-Zhu Chen; Hai-Long Wang; Zhong-Quan Qi; Chang-Long Xu; Yu Liu (Food and Chemical Toxicology, 2023)

What affects the accuracy and applicability of determining wastewater sludge water content via low-field nuclear magnetic resonance? - Ya-Li Zhang; Ping Sun; Bing-Bing Dai; Shao-Ming Zheng; Dan-Di Ran; Tian-Xin Wu; Raymond Jianxiong Zeng; Hou-Feng Wang (Environmental Research, 2023)

Endophytic fungus Trichoderma atroviride D16 increases tanshinone accumulation in Salvia miltiorrhiza plantlets by enhancing abscisic acid and salicylic acid signaling - Xing-Guang Xie; Ke-Xin Sheng; Wei-Lan Lu; Hao-Ran Wang; Khalid Rahman; Kun-Miao Feng; Ting Han (Symbiosis, 2023)

Targeting autophagy receptors OPTN and SQSTM1 as a novel therapeutic strategy for osteoporosis complicated with Alzheimer's disease - Ran Duan; Chun-Gu Hong; Meng-Lu Chen; Xin Wang; Zhi-Lin Pang; Hui Xie; Zheng-Zhao Liu (Chemico-Biological Interactions, 2023)

Two new chemical constituents from the leaves of Illicium dunnianum - Jun-Ran Shao; Sen-Ju Ma; Ting Li; Xiao-Qing He; Zhen-Zhong Wang; Wei Xiao; Xin-Sheng Yao; Hai-Bo Li; Yang Yu (Natural Product Research, 2023)

DNA damage and up-regulation of PARP-1 induced by columbin in vitro and in vivo - Yufen Liao; Xin Wang; Guangyun Ran; Shiyu Zhang; Chutian Wu; Rong Tan; Ying Liu; Yan He; Ting Liu; Zhongxiu Wu; Ying Peng; Weiwei Li; et al. (Toxicology Letters, 2023)

Formation of RNA adducts resulting from metabolic activation of spice ingredient safrole mediated by P450 enzymes and sulfotransferases - Xin Wang; Guangyun Ran; Yufen Liao; Bowen Gong; Chutian Wu; Rong Tan; Ying Liu; Shiyu Zhang; Ying Peng; Weiwei Li; Jiang Zheng (Food and Chemical Toxicology, 2023)

Cobalt chloride exposure disturbs spindle assembly and decreases mouse oocyte development potential - Si-Cheng Zhao; Feng-Xin Qiao; Ming-Xin Sun; Yue-Cen Liu; Hai-Long Wang; Zhi-Ran Xu; Yu Liu (Toxicology, 2023)

Crystal-modeler: A tool for geometric analysis and three-dimensional modeling of crystal forms based on rectangular coordinates in space - Huixia Chao; Yue Li; Weihua Yao; Xin Han; Ran Wang (Earth Science Informatics, 2023)

Triptolide exposure induces oxidative stress and decreases oocyte quality in mouse - Qian-Qian Hao; Zhi-Ran Xu; Han Nie; Feng-Xin Qiao; Ming-Xin Sun; Yue-Cen Liu; Hai-Long Wang; Zhong-Quan Qi; Chang-Long Xu; Yu Liu (Toxicon, 2023)

Soil nitrogen substances and denitrifying communities regulate the anaerobic oxidation of methane in wetlands of Yellow River Delta, China - Zihao Wang; Kun Li; Xiaoyan Shen; Feifei Yan; Xinkun Zhao; Yu Xin; Linhui Ji; Qingyue Xiang; Xinyi Xu; Daijia Li; Junhao Ran; Xiaoya Xu; et al. (Science of The Total Environment, 2023)

3-MCPD exposure enhances ovarian fibrosis and reduces oocyte quality in mice - Quan-Kuo He; Yan-Ping Li; Zhi-Ran Xu; Wen-Bo Wei; Feng-Xin Qiao; Ming-Xin Sun; Yue-Cen Liu; Yan-Zhu Chen; Hai-Long Wang; Zhong-Quan Qi; Yu Liu (Environmental Pollution, 2023)

Effects of oxygen content on gaseous and solid products during molten salt oxidation of cation exchange resins - Yun Xue; Yue-Lin Wang; Yang-Hai Zheng; Yu-Sheng Yang; Wen-Da Xu; Yong-De Yan; Ran Zhao; Qing-Guo Zhang; Xin Liu; Fu-Qiu Ma; Mi-Lin Zhang (Environmental Science and Pollution Research, 2022)

Transplantation of Nasal Olfactory Mucosa Mesenchymal Stem Cells Benefits Alzheimer’s Disease - Chun-Gu Hong; Meng-Lu Chen; Ran Duan; Xin Wang; Zhi-Lin Pang; Li-Te Ge; Ming Lu; Hui Xie; Zheng-Zhao Liu (Molecular Neurobiology, 2022)

Effect of Iron Plaque on Gaseous Elemental Mercury Uptake, Translocation, and Volatilization by Paddy Rice - Yanlin Wang; Shuai Shang; Xin Li; Sinan Chen; Ran Li; Weiwei Jia; Hong Deng (Bulletin of Environmental Contamination and Toxicology, 2022)

Feasibility of Surfgrass Phyllospadix iwatensis Transplantation Along the Rocky Coasts of Shandong Peninsula, China - Jiaxin Zhan; Ran Cheng; Xin Hou; Huan Wang; Peidong Zhang; Bin Kang; Wentao Li (Journal of Ocean University of China, 2022)

Prenylaromadendrane-type diterpenoids from the gum resin of Boswellia sacra flueck and their cytotoxic effects - Jia-Jia Wang; Xin-Yue Suo; Hao-Ran Sun; Xue Wang; Ming-Bao Lin; Jin-Hua Wang; Jian-Dong Jiang; Teng-Fei Ji (Natural Product Research, 2022)

New polymerized sesquiterpene lactones from Ainsliaea yunnanensis and their activity evaluation - Na Zhou; Jin-Jie Li; Yong Wu; Ze-Yu Wang; Xin Wang; Zhi-Peng Yin; Xin-Peng Wang; Yi-Ran Liu; Xiao-Ya Shang (Natural Product Research, 2022)

Therapeutic effect of the sulforaphane derivative JY4 on ulcerative colitis through the NF-κB-p65 pathway - Xiu-Juan Zhao; Yi-Ran Zhang; Wen-Fei Bai; Tong-Yan Sun; Yu-Fen Yang; Tong-Xin Wang; Cui-Gai Bai (Inflammopharmacology, 2022)

Stat5−/− CD4+ T cells elicit anti-melanoma effect by CD4+ T cell remolding and Notch1 activation - Ke Jin; Tong Li; Zhiyong Miao; Jingjing Ran; Luyu Chen; Dachao Mou; Chuang Wang; Shasha Wu; Hanshuo Yang; Xin-Yuan Fu (Science China Life Sciences, 2022)

Dyadobacter diqingensis sp. nov., isolated from Baima snow mountain of Diqing Tibetan Autonomous Prefecture in Yunnan province, south-west China - Lei Ran; Man Peng; Wei-Qun Wang; Yu-Zhou Feng; Juan Wang; Yu Wang; Cui-Ying Li; Xin-Xing Liu; Wei-Xun Chunyu; Shu-Kun Tang (Archives of Microbiology, 2022)

Potential of phytomedicine in the treatment of inflammatory bowel disease - Jie Tang; Dong Xu; Xin-Ran Dong; Yi-Lun Wang; Kun-Tang Wang; Yue Wang; Tao Qiao; Yuan-Lu Cui (Phytochemistry Reviews, 2022)

Investigation on long-term progressive deformation of engineering slope based on comprehensive monitoring - Shi-shu Zhang; Song-feng Guo; Sheng-wen Qi; Feng-jiao Tang; Jin-shan Hu; Xiao-ping Zhao; Cong-yan Ran; Xin Wang; Yu Zou; Xiao-lin Huang; Bo-wen Zheng; Ning Liang (Journal of Mountain Science, 2022)

Terrestrial carbon cycle model-data fusion: Progress and challenges - Xin Li; Hanqing Ma; Youhua Ran; Xufeng Wang; Gaofeng Zhu; Feng Liu; Honglin He; Zhen Zhang; Chunlin Huang (Science China Earth Sciences, 2021)

Generation and identification of endothelial-specific Hrh2 knockout mice - Rui Meng; Wen-Ke Cai; Wen-Mang Xu; Qiang Feng; Ping Wang; Yan-hua Huang; Yu-Xin Fan; Tao Zhou; Qin Yang; Zhi-Ran Li; Gong-Hao He (Transgenic Research, 2021)

Marinobacter caseinilyticus sp. nov., Isolated from Saline Soil - Yanfang Nie; Xin Su; Dildar Wu; Ran Zhang; Ruijun Wang; Zhe Zhao; Maripat Xamxidin; Cong Sun; Min Wu (Current Microbiology, 2021)

Apple MdSAT1 encodes a bHLHm1 transcription factor involved in salinity and drought responses - Yu-Ying Yang; Peng-Fei Zheng; Yi-Ran Ren; Yu-Xin Yao; Chun-Xiang You; Xiao-Fei Wang; Yu-Jin Hao (Planta, 2021)

Estimation of the longitudinal dispersion coefficient using a two-zone model in a channel partially covered with artificial emergent vegetation - Jiao Zhang; Wen-Xin Huai; Hao-Ran Shi; Wei-Jie Wang (Environmental Fluid Mechanics, 2021)

Interactions between invasive fungi and symbiotic bacteria - Fen Wang; Caiyan Xin; Jiexing Liu; Zhuonan Ran; Chunling Zhao; Zhangyong Song (World Journal of Microbiology and Biotechnology, 2020)

Correction to: AVE0991, a nonpeptide angiotensin-(1–7) mimic, inhibits angiotensin II–induced abdominal aortic aneurysm formation in apolipoprotein E knockout mice - Hui Ma; Yu-Lin Wang; Nai-Hao Hei; Jun-Long Li; Xin-Ran Cao; Bo Dong; Wen-jiang Yan (Journal of Molecular Medicine, 2020)

AVE0991, a nonpeptide angiotensin-(1–7) mimic, inhibits angiotensin II–induced abdominal aortic aneurysm formation in apolipoprotein E knockout mice - Hui Ma; Yu-Lin Wang; Nai-Hao Hei; Jun-Long Li; Xin-Ran Cao; Bo Dong; Wen-jiang Yan (Journal of Molecular Medicine, 2020)

Correction to: Description of Wenzhouxiangella salilacus sp. nov., a moderate halophilic bacterium isolated from a salt lake in Xinjiang Province, China - Shuai-Bo Han; Xin-Jun Hou; Yang-Huan Yu; Zhao Ju; Ran Zhang; Rui-Jun Wang; Yang-Hui Ye; Yan-Hu Ren; Wei-Yan Zhang; Min Wu (Antonie van Leeuwenhoek, 2020)

Anaerophilus nitritogenes gen. nov., sp. nov., isolated from salt lake sediment in Xinjiang Province, China - Ran Zhang; Yan Zeng; Tian-Qi Wang; Xin-Mei Wang; Yi-Yu Shi; Jia-Tian Zou; Cong Sun; Gui-Shan Zhang; Wei-Yan Zhang; Min Wu (Antonie van Leeuwenhoek, 2020)

Characterization and differential expression of microRNA in the freshwater shrimp ( Neocaridina heteropoda ) with different body length - Ran Li; Xin Wang; Qinghao Meng; Liqi Ren; Jieyang Weng; Shen Wang; Jinsheng Sun (Invertebrate Reproduction & Development, 2020)

Description of Wenzhouxiangella salilacus sp. nov., a moderate halophilic bacterium isolated from a salt lake in Xinjiang Province, China - Shuai-Bo Han; Xin-Jun Hou; Yang-Huan Yu; Zhao Ju; Ran Zhang; Rui-Jun Wang; Yang-Hui Ye; Yan-Hu Ren; Wei-Yan Zhang; Min Wu (Antonie van Leeuwenhoek, 2019)

Novel technologies applied for recovery and value addition of high value compounds from plant byproducts: A review - Xin-li Ran; Min Zhang; Yuchuan Wang; Benu Adhikari (Critical Reviews in Food Science and Nutrition, 2019)

Mild Hypothermia Prevents NO-Induced Cytotoxicity in Human Neuroblastoma Cells Via Induction of COX-2 - Bing-Bing Lei; Fei Ju; Qi-Ran Fu; Xin Yuan; Wen-Xin Song; Guo-Qin Ji; Kai-Yu Lei; Lei Wang; Bin-Feng Cheng; Mian Wang; Hai-Jie Yang (Journal of Molecular Neuroscience, 2019)

Old method not old-fashioned: parallelism between wing venation and wing-pad tracheation of cockroaches and a revision of terminology - Xin-Ran Li; Yu-Hong Zheng; Chen-Chen Wang; Zong-Qing Wang (Zoomorphology, 2018)

Discovery of potent and selective acetylcholinesterase (AChE) inhibitors: acacetin 7- O -methyl ether Mannich base derivatives synthesised from easy access natural product naringin - Hao-ran Liu; Xue Men; Xiao-hui Gao; Lin-bo Liu; Hao-qun Fan; Xin-hua Xia; Qiu-an Wang (Natural Product Research, 2018)

Asymmetric effects of litter removal and litter addition on the structure and function of soil microbial communities in a managed pine forest - Qiong Zhao; Aimée T. Classen; Wei-Wei Wang; Xin-Ran Zhao; Bing Mao; De-Hui Zeng (Plant and Soil, 2017)

miR-143 regulates proliferation and differentiation of bovine skeletal muscle satellite cells by targeting IGFBP5 - Wei Ran Zhang; Hui Na Zhang; Yi Min Wang; Yang Dai; Xin Feng Liu; Xin Li; Xiang Bin Ding; Hong Guo (In Vitro Cellular & Developmental Biology - Animal, 2017)

Complete genome sequence and comparative genome analysis of a new special Yersinia enterocolitica - Guoxiang Shi; Mingming Su; Junrong Liang; Ran Duan; Wenpeng Gu; Yuchun Xiao; Zhewen Zhang; Haiyan Qiu; Zheng Zhang; Yi Li; Xiaohe Zhang; Yunchao Ling; et al. (Archives of Microbiology, 2016)

Exendin-4 Enhances Motor Function Recovery via Promotion of Autophagy and Inhibition of Neuronal Apoptosis After Spinal Cord Injury in Rats - Hao-Tian Li; Xing-Zhang Zhao; Xin-Ran Zhang; Gang Li; Zhi-Qiang Jia; Ping Sun; Ji-Quan Wang; Zhong-Kai Fan; Gang Lv (Molecular Neurobiology, 2016)

Methane and nitrous oxide emissions under no‐till farming in China: a meta‐analysis - Xin Zhao; Sheng‐Li Liu; Chao Pu; Xiang‐Qian Zhang; Jian‐Fu Xue; Ran Zhang; Yu‐Qiao Wang; Rattan Lal; Hai‐Lin Zhang; Fu Chen (Global Change Biology, 2016)
No‐till ( NT ) practices are among promising options toward adaptation and mitigation of climate change. However, the mitigation effectiveness of NT depends not only on its carbon sequestration potential but also on soil‐derived CH 4 and N 2 O emissions. A meta‐analysis was conducted, using a dataset involving 136 comparisons from 39 studies in China, to identify site‐specific factors which influence CH 4 emission, CH 4 uptake, and N 2 O emission under NT . Comparative treatments involved NT without residue retention ( NT 0), NT with residue retention ( NTR ), compared to plow tillage ( PT ) with residue removed ( PT 0). Overall, NT 0 significantly decreased CH 4 emission by ~30% ( P 0.05) compared to PT 0 with an average emission 218.8 kg ha −1 for rice paddies. However, the increase in N 2 O emission could partly offset the benefits of the decrease in CH 4 emission under NT compared to PT 0. NTR significantly enhanced N 2 O emission by 82.1%, 25.5%, and 20.8% ( P 0.05) compared to PT 0 for rice paddies, acid soils, and the first 5 years of the experiments, respectively. The results from categorical meta‐analysis indicated that the higher N 2 O emission could be mitigated by adopting NT within alkaline soils, for long‐term duration, and with less N fertilization input when compared to PT 0. In addition, the natural log (lnR) of response ratio of CH 4 and N 2 O emissions under NT correlated positively (enhancing emission) with climate factors (temperature and precipitation) and negatively (reducing emission) with experimental duration, suggesting that avoiding excess soil wetness and using NT for a long term could enhance the benefits of NT . Therefore, a thorough understanding of the conditions favoring greenhouse gas(es) reductions is essential to achieving climate change mitigation and advancing food security in China.

microRNA-128 regulates the proliferation and differentiation of bovine skeletal muscle satellite cells by repressing Sp1 - Yang Dai; Wei Ran Zhang; Yi Min Wang; Xin Feng Liu; Xin Li; Xiang Bin Ding; Hong Guo (Molecular and Cellular Biochemistry, 2016)

Calmodulin kinase II inhibitor regulates calcium homeostasis changes caused by acute β-adrenergic receptor agonist stimulation in mouse ventricular myocytes - Yan Huang; Tao Liu; Dandan Wang; Xin Wang; Ran Li; Yuting Chen; Yanhong Tang; Teng Wang; Congxin Huang (In Vitro Cellular & Developmental Biology - Animal, 2016)

Paenibacillus chinensis sp. nov., isolated from maize (Zea mays L.) seeds - Yang Liu; Ran Zhao; Ronghuan Wang; Su Yao; Lei Zhai; Xin Zhang; Chuanyong Chen; Yanhua Cao; Tianjun Xu; Yuanyuan Ge; Jiuran Zhao; Chi Cheng (Antonie van Leeuwenhoek, 2016)

The role of microRNA-1 and microRNA-206 in the proliferation and differentiation of bovine skeletal muscle satellite cells - Yang Dai; Yi Min Wang; Wei Ran Zhang; Xin Feng Liu; Xin Li; Xiang Bin Ding; Hong Guo (In Vitro Cellular & Developmental Biology - Animal, 2016)

Retraction Note to: Genetic variations in the KIR gene family may contribute to susceptibility to ankylosing spondylitis: a meta-analysis - Hai-Ning Zuo; Zhi-Long Wang; Dao-Ran Cui; Da-Jiang Xin (Molecular Biology Reports, 2015)

Associations Between ApoEε4 Carrier Status and Serum BDNF Levels—New Insights into the Molecular Mechanism of ApoEε4 Actions in Alzheimer’s Disease - Yu-Hui Liu; Shu-Sheng Jiao; Ye-Ran Wang; Xian-Le Bu; Xiu-Qing Yao; Yang Xiang; Qing-Hua Wang; Lin Wang; Juan Deng; Jing Li; Xin-Fu Zhou; Hua-Dong Zhou; et al. (Molecular Neurobiology, 2015)

Protective Effects of Poly (butyl) Cyanoacrylate Nanoparticles Containing Vasoactive Intestinal Peptide Against 6-Hydroxydopamine-Induced Neurotoxicity In Vitro - Zhi-Ran Xu; Wu-Fang Wang; Xin-Fang Liang; Ze-Hua Liu; Yu Liu; Liang Lin; Xuan Zhu (Journal of Molecular Neuroscience, 2015)

Clearance of Amyloid-Beta in Alzheimer’s Disease: Shifting the Action Site from Center to Periphery - Yu-Hui Liu; Ye-Ran Wang; Yang Xiang; Hua-Dong Zhou; Brian Giunta; Noralyn B. Mañucat-Tan; Jun Tan; Xin-Fu Zhou; Yan-Jiang Wang (Molecular Neurobiology, 2015)

Paradevosia shaoguanensis gen. nov., sp. nov., Isolated from a Coking Wastewater - Shuang Geng; Xin-Chi Pan; Ran Mei; Ya-Nan Wang; Ji-Quan Sun; Xue-Ying Liu; Yue-Qin Tang; Xiao-Lei Wu (Current Microbiology, 2015)

Identification of a Novel Mutation in the Presenilin 1 Gene in a Chinese Alzheimer’s Disease Family - Bo Deng; Yan Lian; Xin Wang; Fan Zeng; Bin Jiao; Ye-Ran Wang; Chun-Rong Liang; Yu-Hui Liu; Xian-Le Bu; Xiu-Qing Yao; Chi Zhu; Lu Shen; et al. (Neurotoxicity Research, 2014)

SNAP25 Ameliorates Sensory Deficit in Rats with Spinal Cord Transection - Wei Wang; Fang Wang; Jia Liu; Wei Zhao; Qi Zhao; Mu He; Bao-Jiang Qian; Yang Xu; Ran Liu; Su-Juan Liu; Wei Liu; Jin Liu; et al. (Molecular Neurobiology, 2014)

Nitratireductor shengliensis sp. nov., Isolated from an Oil-Polluted Saline Soil - Xin-Chi Pan; Shuang Geng; Ran Mei; Ya-Nan Wang; Hua Cai; Xue-Ying Liu; Yue-Qin Tang; Yong Nie; Si-Yuan Ye; Xiao-Lei Wu (Current Microbiology, 2014)

RETRACTED ARTICLE: Genetic variations in the KIR gene family may contribute to susceptibility to ankylosing spondylitis: a meta-analysis - Hai-Ning Zuo; Zhi-Long Wang; Dao-Ran Cui; Da-Jiang Xin (Molecular Biology Reports, 2014)

The Pseudomonas aeruginosa Mannose Sensitive Hamemagglutination Strain (PA-MSHA) Induces a Th1-Polarizing Phenotype by Promoting Human Dendritic Cells Maturation - Yunyan Zhang; Hongtao Wang; Youqiang Li; Ke Chen; Jinmei Ye; Xin Liao; Yiyang Chen; Wei Ran (Indian Journal of Microbiology, 2014)

Ottowia shaoguanensis sp. nov., Isolated From Coking Wastewater - Shuang Geng; Xin-Chi Pan; Ran Mei; Ya-Nan Wang; Ji-Quan Sun; Xue-Ying Liu; Yue-Qin Tang; Xiao-Lei Wu (Current Microbiology, 2014)

Lipopolysaccharides Reduce Adipogenesis in 3T3-L1 Adipocytes Through Activation of NF-κB Pathway and Downregulation of AMPK Expression - Lifeng Wang; Linlin Li; Xinjian Ran; Mei Long; Minfang Zhang; Yicun Tao; Xin Luo; Ye Wang; Yi Jiao; Xinmin Mao; Jun Ren (Cardiovascular Toxicology, 2013)

The Antitumor Effect of a New Docetaxel-Loaded Microbubble Combined with Low-Frequency Ultrasound In Vitro: Preparation and Parameter Analysis - Shu-Ting Ren; Yi-Ran Liao; Xiao-Ning Kang; Yi-Ping Li; Hui Zhang; Hong Ai; Qiang Sun; Jing Jing; Xing-Hua Zhao; Li-Fang Tan; Xin-Liang Shen; Bing Wang (Pharmaceutical Research, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Functional recombinant human anti-HBV antibody expressed in milk of transgenic mice - Ran Zhang; Dan Cui; Hong Wang; Chuan Li; Xin Yao; Yaofeng Zhao; Mifang Liang; Ning Li (Transgenic Research, 2012)

Sucrose monolaurate synthesis with Protex 6L immobilized on electrospun TiO2 nanofiber - Xin-Ran Wang; Song-Ping Zhang; Ping Wang (Biotechnology Letters, 2011)

The Prevalence of Type 2 Diabetes and Hypertension in Uygur and Kazak Populations - Yicun Tao; Xinmin Mao; Zijing Xie; Xinjian Ran; Xiaoyan Liu; Ye Wang; Xin Luo; Mengying Hu; Wenning Gen; Minfang Zhang; Tao Wang; Jun Ren; et al. (Cardiovascular Toxicology, 2008)

Analysis of Prevalence and Risk Factors of Hypertension Among Uygur Adults in Tushala and Hetian Xinjiang Uygur Autonomous Region - Lin-Lin Li; Xiao-Yan Liu; Jian-Xin Ran; Ye Wang; Xin Luo; Tao Wang; Jun Ren; Mayinuer Aisha; Rebiya Abudureheman; Adalaiti Xiawudong; Xiao-Chun Zhang; Xin-Min Mao (Cardiovascular Toxicology, 2008)